Three consecutive cases of fatal intraoperative intracardiac thrombosis associated with the initiation of venoarterial extracorporeal membrane oxygenation in the presence of aprotinin. (July 2019) - Oscier, Chris; Patvardhan, Chinmay; Falter, Florian; Tosh, Will; Dunning, John; Catarino, Pedro; DeSilva, Ravi; Besser, Martin; Valchanov, Kamen
Central venoarterial extracorporeal membrane oxygenation has been used since the 1970s to support patients with cardiogenic shock following cardiac surgery. Despite this, in-hospital mortality is still high, and although rare, thrombus within the cardiac chambers or within the extracorporeal membrane oxygenation circuit is often fatal. Aprotinin is an antifibrinolytic available in Europe and Canada, though not currently in the United States. Due to historical safety concerns, use of aprotinin is generally limited and is commonly reserved for patients with the highest bleeding risk. Given the limited availability of aprotinin over the last decade, it is not surprising to find a complete absence of literature describing the use of venoarterial extracorporeal membrane oxygenation in the presence of aprotinin. We present three consecutive cases of rapid fatal intraoperative intracardiac thrombosis associated with post-cardiotomy central venoarterial extracorporeal membrane oxygenation in patients receiving aprotinin.